To represent Plant A’s height after \( t \) months, we can use the following expression:
\[ \text{Height of Plant A} = 25 + 8t \]
Where:
- 25 cm is the starting height of Plant A.
- 8 cm is the growth rate per month.
- \( t \) represents the number of months.
Similarly, we can write an expression for Plant B’s height after \( t \) months:
\[ \text{Height of Plant B} = 10 + 13t \]
Where:
- 10 cm is the starting height of Plant B.
- 13 cm is the growth rate per month.
To find out after how many months the plants will be the same height, we need to set the two expressions equal to each other:
\[ 25 + 8t = 10 + 13t \]
Now, we will solve for \( t \):
-
Subtract \( 8t \) from both sides: \[ 25 = 10 + 5t \]
-
Subtract 10 from both sides: \[ 15 = 5t \]
-
Divide by 5: \[ t = 3 \]
Now that we have \( t = 3 \), we can find the height of the plants at this time by substituting \( t \) back into either height expression.
Using Plant A’s expression: \[ \text{Height of Plant A} = 25 + 8(3) = 25 + 24 = 49 \text{ cm} \]
Using Plant B’s expression: \[ \text{Height of Plant B} = 10 + 13(3) = 10 + 39 = 49 \text{ cm} \]
Thus, after 3 months, both Plant A and Plant B will be the same height of 49 cm.
In summary:
- They will be the same height after 3 months.
- At that time, their height will be 49 cm.